Owner Behaviours toward the Livestock between Required and Available: a Scientific Review - Alabbody, Huda Hameed Kadhim (American Journal of Biology and Natural Sciences, 2025)
Livestock farming plays a vital role in food production and rural livelihoods; however, owner practices significantly impact herd health and productivity. This study identifies gaps in livestock management by evaluating owner behaviors toward preventive healthcare, nutrition, and disease management based on previous field studies in Iraq. Findings indicate that while some owners follow parasite control measures, many neglect vaccination programs, veterinary consultations, and proper feeding practices, leading to high disease prevalence and economic losses. The results highlight the need for enhanced education and support systems to improve herd health management. Implementing structured training and government-backed agricultural extension programs can significantly improve livestock productivity and sustainability.